THE PROCESS OF ALKYNYLATION OF SOME HETEROATOMIC ALDEHYDES WITH ALKYNES IN THE PRESENCE OF THE InBr3/Et3N/Et2O CATALYTIC SYSTEM (Scientific journal of the Fergana State University, 2024)
Aldehydes containing in their molecule heteroatom‒ thiophene-2-carbaldehyde, 3-methylthiophene-2-carbaldehyde, furan-2 carbaldehyde, pyridine-3-carbaldehyde, quinoline-2-carbaldehyde and 3-bromine-4 pyridine carbaldehyde with acetylene, phenylacetylene, hexin-1, octin-1 were synthesized for the first time acetylene alcohols using the InBr3/Et3N/Et2O catalytic system. The influence of molar quantitative ratios of starting substances, reaction duration, temperature, nature of the catalyst and solvents on the yield of the product was systematically studied. The composition, frequency and structure of synthesized acetylene alcohols of a new generation have been proven by modern physicochemical methods.